Anesthesiologic Provision of Osteosynthesis of the Neck of the Femur in Geriatric Patients - O. V. Lapin; Yu. V. Nikiforov; V. V. Konstantinov (Общая реаниматология)
The purpose of the study was to evaluate the clinical efficiency of femoral 3 in 1 block using the solution of a local anesthetic in combination with an opioid versus central regional (spinal) anesthesia during operation involving osteosynthesis of the neck of the femur with cannulated screws in geriatric patients. Osteosynthesis of the neck of the femur with cannulated screws proposed by the Osteosynthesis Association (OA) was performed in 90 patients (33 males and 57 females) aged 65 to 90 (71.0±5.026) years. Two procedures were used for the anesthe-siological provision of the operation. The osteosynthesis was made in 65 patients under central regional (spinal) anesthesia (Group 1) and in 25 patients under femoral 3 in 1 block employing the solution of a local anesthetic in combination with an opioid (Group 2). Both groups were matched by age, gender, anthropometric data, and the pattern of concomitant diseases. Analysis of the findings revealed that in 40% of cases, operations made under spinal anesthesia (Group 1) used adrenomimetics: ephedrine, 0.2—0.4 mg/kg, or dopamine, 3—5 ^g^kg/min; the total infusion volume was 2254±162 ml. Colloid agents (polyglucin, 6% infucol, or 6% refortan solutions) were given to 23 (36%) of the 65 patients. The reduction in mean blood pressure was 26.3% of the baseline. Group 2 did not require the use of colloidal and/or adrenomimetics. The mean intraoperative infusion volume was 1146±109.3 ml. During surgery, hemodynamics remained stable in all the patients. All Group 1 patients operated on under spinal anesthesia experienced postoperative pain whose relief required the use of nonsteroidal anti-inflammatory drugs (ketorol, ketonal, baralgin) and opioids (promedole, omnopon), 44% of cases requiring multiple administration of narcotic analgesics within the first and second postoperative days. Analysis of the postoperative period indicated a good analgesia in the patients operated on under femoral 3 in 1 block with local anesthetic solution in combination with an opioid. At a rest, all Group 2 patients did not observe no painful sensations at the site of surgery. Thus, femoral 3 in 1 block with 40 ml of 0.25% marcaine and 10 mg of morphine hydrochloride is an effective and safe anesthesiological support in geriatric patients during operations involving the osteosynthesis with OA cannulated screws. Perineutal administration of 10 mg of morphine hydrochloride provides a good postoperative analgesia, which is an important factor in preventing cardiorespiratory complications in patients to be surgically treated.